2022
DOI: 10.1017/pasa.2022.20
|View full text |Cite
|
Sign up to set email alerts
|

Infrared study of the star-forming region associated with the UC HII regions G45.07+0.13 and G45.12+0.13

Abstract: Ultra-compact H ii (UC HII) regions are an important phase in the formation and early evolution of massive stars and a key component of the interstellar medium (ISM). The main objectives of this work are to study the young stellar population associated with the G45.07+0.13 and G45.12+0.13 UC HII regions, as well as the ISM in which they are embedded. We determined the distribution of the hydrogen column density (N( $\mathrm{H}_2$ )) and dust temperature ( $T_d$ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 88 publications
(138 reference statements)
1
7
0
Order By: Relevance
“…The c-m diagram shows that the cluster members are well above the photometric limit. Indeed, no objects with a mass equal to or less than 1.4 M ⊙ were found in Azatyan et al (2022). For comparison, it should be noted that no such phenomenon is observed in the IRAS 5168+3634 region.…”
Section: Comparative Analysis Of Two Star-forming Regionmentioning
confidence: 94%
See 4 more Smart Citations
“…The c-m diagram shows that the cluster members are well above the photometric limit. Indeed, no objects with a mass equal to or less than 1.4 M ⊙ were found in Azatyan et al (2022). For comparison, it should be noted that no such phenomenon is observed in the IRAS 5168+3634 region.…”
Section: Comparative Analysis Of Two Star-forming Regionmentioning
confidence: 94%
“…Using the Modified blackbody fitting on the Herschel images it was found that N(H 2 ) varies from 3.0 x 10 23 to 5.5 x 10 23 cm −2 within the G45.07+0.13 and G45.12+0.13 regions (Azatyan et al, 2022). The maximum T d values are 35 K in G45.12+0.13 and 42 K in G45.07+0.13.…”
Section: Iras 05168+3634 Regionmentioning
confidence: 99%
See 3 more Smart Citations